Antibiotic resistance and residue in chicken, cattle, buffalo and goat meats in different southern districts of Bangladesh - Matubber, Bidyut; Rume, Farzana Islam; Hoque Kayesh, Mohammad Enamul; Rahman, Mohammad Mahfuzur; Amin, Mohammad Rohul; Asgar, Md Ali; Anower, A K M Mostafa (Asian-Australasian Journal of Food Safety and Security, 2021)
The presence of antibiotic residue in chicken and animal meats is a serious threat to human health due to its harmful effects. This study aimed at identifying the antibiotic resistance patterns of the isolates as well as antibiotic residues in chicken, cattle, buffalo and goat meats in different southern districts of Bangladesh. A total of 205 meat samples, including 70 chicken meat, 60 cattle meat, 50 buffalo meat and 25 goat meat were aseptically collected and analysed for the detection of antibiotic residues by thin layer chromatography and the isolates obtained from these samples were subjected to antibiogram study against 16 commonly used antibiotics. The isolates found in this study were Staphylococcus spp., Streptococcus spp., Escherichia coli, and Salmonella spp. and their prevalence were 37.5% (77/205), 22.1% (48/205), 29.7% (61/205), 8.7% (19/205), respectively. The isolates showed different degrees of sensitivity to the antibiotics used in the study. The most resistant phenotype was against cefradine, amoxicillin, penicillin, oxytetracycline, erythromycin, and enrofloxacin. 18.5% (38/205) meat samples were found to be positive for antibiotic residues and the highest prevalence was observed in chicken meat compared to other meat types. Overall, the findings of the study suggest that it is important to take controlling measures for the emergence of antibiotic resistance and also for ensuring healthy meats for human consumption. Asian Australas. J. Food Saf. Secur. 2021, 5 (1), 19-26